Quantum dot material and preparation method, quantum dot light emitting diode and preparation method
By performing ligand exchange and ester hydrolysis reaction on the surface of quantum dots, linear organic carboxylic acid ligands are generated, which solves the problem of poor contact between quantum dots and ZnO, improves the electrical performance and luminous efficiency of the quantum dot film, and extends the device life .
Patent Information
- Application Number
- CN202010591352.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-24
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-06-24
AI Technical Summary
Quantum dot electroluminescent devices have problems with low efficiency and short life. This is mainly due to the poor contact between the quantum dot surface and ZnO, which leads to difficulty in injection of electrons, incomplete layer structure, and many defects, which affects electrical performance.
Using ligand exchange method to bind compound A on the surface of quantum dots, the linear organic carboxylic acid ligand is generated through ester hydrolysis reaction, which improves surface properties, enhances contact performance with electron transport layer, and forms a QDs/ETL interface containing metal ions, which promotes the Injection of electrons to reduce charge accumulation and stress.
It improves the optical performance and luminous efficiency of the quantum dot film, extends the service life of the device, and achieves a high-quality multi-layer film structure.
Smart Images

Figure CN113831908B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of display technology, and in particular relates to a quantum dot material and a preparation method thereof, as well as a quantum dot light emitting diode and a preparation method thereof. Background Art
[0002] Quantum dots, also known as semiconductor nanocrystals, are usually composed of II-VI or III-V elements, and their particle size is less than or close to the exciton Bohr radius. After nearly 30 years of research and development, the development of quantum dot synthesis technology has made significant breakthroughs. Among them, the research on II-VI quantum dots represented by CdSe has been perfected, such as: the photoluminescence efficiency is close to 100%, the peak width is as narrow as 20-30nm, and the device efficiency and device life of red and green quantum dots are close to the requirements of commercial applications. Since high-quality quantum dots are synthesized by all-solution methods, they are very suitable for film preparation by solution processing methods such as spin coating and printing. Therefore, QLEDs with quantum dots as the light-emitting layer are expected to become a strong competitor for the next generation of new display technologies.
[0003] However, quantum dot electroluminescent devices still have problems such as low efficiency and short life, and the spin coating technology commonly used to build high-efficiency QLED devices usually uses ZnO as the electron transport layer (ETL) of QLED. However, since the surface of quantum dots is non-polar and has poor contact with ZnO, electron injection is difficult, the surface structure of quantum dots is chaotic and disordered, the superlattice structure of the quantum dot layer is incomplete, has many defects, and has low order, which makes the electrical performance of the quantum dot film poor. In addition, the device electron mobility is much higher than the hole mobility, which makes the charge accumulation phenomenon at the QD / ETL interface very serious, which has a very adverse effect on the efficiency and life of QLED devices. Summary of the invention
[0004] The purpose of the present invention is to provide a quantum dot film and a preparation method thereof, aiming to solve the problem of poor electrical performance of the existing quantum dot film.
[0005] Another object of the present invention is to provide a quantum dot light emitting diode containing the above quantum dot film.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0007] A first aspect of the present invention provides a method for preparing a quantum dot film, comprising the following steps:
[0008] Under an inert atmosphere, a fatty acid solution of compound A and a mixed solution system of first quantum dots are provided, and a ligand exchange reaction is performed under a first heating condition to prepare second quantum dots with compound A bound to the surface; wherein the general structural formula of compound A is as follows: 1is the first active group combined with the first quantum dot; R 1 -(CH2) n -, R 2 For straight chain C m H 2m+1 , m and n are positive integers, and the value of n+m ranges from 2 to 12;
[0009]
[0010] A substrate is provided, and the second quantum dots are deposited on the substrate to prepare a quantum dot prefabricated film; a mixed solution containing an ester hydrolysis catalyst is deposited on the quantum dot prefabricated film, and the mixture is heated to cause the compound A at least on the surface of the quantum dot prefabricated film to undergo an ester hydrolysis reaction to generate a first ligand, thereby preparing a quantum dot film; or the second quantum dots are mixed with a mixed solution containing an ester hydrolysis catalyst, and the mixture is heated to cause the compound A on the surface of the second quantum dots to undergo an ester hydrolysis reaction to generate a first ligand having a general structural formula X 1 -CH2-R 1 -COOH first ligand, obtain second quantum dots with the first ligand bound to the surface, and perform film forming treatment on a substrate to prepare a quantum dot film.
[0011] The second aspect of the present invention provides a quantum dot film, the quantum dot film is composed of quantum dots, the quantum dots include a quantum dot matrix, a first ligand bound to the surface of the quantum dot matrix, and at least one of a second ligand, a third ligand, and a fourth ligand bound to the surface of the quantum dot matrix, wherein the first ligand is X 1 -CH2-R 1 -COOH, X 1 is the first active group combined with the first quantum dot; R 1 -(CH2) n -, n is a positive integer, and the value of n is in the range of 1 to 10.
[0012] The third aspect of the present invention provides a quantum dot light-emitting diode, comprising an anode and a cathode arranged relatively to each other, a quantum dot light-emitting layer arranged between the cathode and the anode, and an electron transport layer arranged between the quantum dot light-emitting layer and the cathode, wherein the quantum dot light-emitting layer is a preparation method of a quantum dot film obtained by the above-mentioned preparation method; or the quantum dot light-emitting layer is the above-mentioned quantum dot film.
[0013] A fourth aspect of the present invention provides a method for preparing a quantum dot light-emitting diode, which at least includes preparing a quantum dot light-emitting layer, and the quantum dot light-emitting layer is prepared by the above-mentioned preparation method.
[0014] The preparation method of the quantum dot film provided by the present invention uses a ligand exchange method to first bind compound A on the surface of the quantum dot, and after film formation, the ester group of the ligand on the surface of the quantum dot layer is converted into a first ligand-a straight-chain organic carboxylic acid through a hydrolysis reaction. The quantum dot film thus obtained can improve its surface properties, thereby improving the contact performance with the adjacent layer material, and further improving the optical performance.
[0015] The quantum dot film provided by the present invention is composed of quantum dots, and the surface of the quantum dots is at least combined with a general structure of X 1 -CH2-R 1 The quantum dot film provided by the method can improve its surface properties, thereby improving the contact performance with the adjacent layer materials and further improving the optical performance.
[0016] The quantum dot light-emitting diode provided by the present invention uses the above-mentioned quantum dot film as the light-emitting layer, and the first ligand on the quantum dots on the surface of the quantum dot film combines with the metal oxide in the electron transport layer to form a QDs / ETL interface containing metal ions, so that the binding force between the quantum dots and the electron transport layer is enhanced, the contact angle is reduced, and a mixed phase interface or an interface with very small intrinsic interface tension is formed, which is conducive to the injection of electrons from the electron transport layer into the quantum dots, reduces the charge accumulation at the QD / ZnO interface and the device damage and attenuation caused by stress, so that the service life and luminous efficiency of the device are improved. Therefore, the luminous efficiency and service life of the device can be effectively improved.
[0017] The method for preparing a quantum dot light-emitting diode provided by the present invention comprises the following steps: when a quantum dot film contacts a metal compound in an electron transport layer, a straight-chain organic carboxylic acid obtained by hydrolysis of compound A combines with metal ions to obtain a quantum dot surface of quantum dot-first ligand-metal ion, thereby forming a QDs / ETL interface containing metal ions with a metal oxide in the electron transport layer, especially zinc oxide, so that the binding force between the quantum dot and the electron transport layer is enhanced, the contact angle is reduced, a mixed phase interface or an interface with very small intrinsic tension is formed, which is conducive to the injection of electrons from the electron transport layer into the quantum dot, reduces charge accumulation at the QD / ZnO interface and device damage and attenuation caused by stress, thereby improving the device service life and luminous efficiency, and is of great significance for realizing a high-quality and strong-binding multilayer film structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0019] Figure 1 is a process flow chart of preparing a quantum dot film provided by an embodiment of the present invention;
[0020] Figure 2 It is a schematic diagram of the ligand exchange reaction between monomethyl suberate provided in an embodiment of the present invention and oleic acid, an initial ligand on the surface of quantum dots;
[0021] Figure 3 is a schematic diagram of a ligand exchange reaction between 9-nitroanthracene provided in an embodiment of the present invention and quantum dots combined with monomethyl suberate;
[0022] Figure 4 It is a schematic diagram of the quantum dot light-emitting layer and the interface between the quantum dot light-emitting layer and the hole transport layer (HTL) and the electron transport layer (ETL) after the quantum dot film is formed using 9-nitroanthracene and suberic acid as ligands provided in an embodiment of the present invention;
[0023] Figure 5 It is a schematic diagram of the quantum dot light-emitting layer and the interface between the quantum dot light-emitting layer and the hole transport layer (HTL) and the electron transport layer (ETL) after the quantum dot film is formed using suberic acid and hydroxyethyl methacrylate (HEMA) as ligands at the same time, provided in an embodiment of the present invention;
[0024] Figure 6 It is a schematic diagram of the quantum dot light-emitting layer and the interface between the quantum dot light-emitting layer and the hole transport layer (HTL) and the electron transport layer (ETL) after the quantum dot film is formed using suberic acid and 1,3,5-tri(4-carboxyphenyl)benzene as ligands at the same time, provided in an embodiment of the present invention;
[0025] Figure 7 It is a schematic diagram of the structure of a quantum dot light emitting diode provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0028] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0029] like Figure 1 As shown, a first aspect of an embodiment of the present invention provides a method for preparing a quantum dot film, comprising the following steps:
[0030] S01. Under an inert atmosphere, a fatty acid solution of compound A and a mixed solution system of the first quantum dots are provided, and a ligand exchange reaction is performed under a first heating condition to prepare a second quantum dot having compound A bound to the surface; wherein the general structural formula of compound A is as follows, X 1 is the first active group combined with the first quantum dot; R 1 -(CH2) n -, R 2 For straight chain C m H 2m+1 , m and n are positive integers, and the value of n+m ranges from 2 to 12;
[0031]
[0032] S02. Providing a substrate, depositing a second quantum dot on the substrate to prepare a quantum dot prefabricated film; depositing a mixed solution containing an ester hydrolysis catalyst on the quantum dot prefabricated film, heating to cause at least the compound A on the surface of the quantum dot prefabricated film to undergo an ester hydrolysis reaction to generate a compound having a general structure of X 1 -CH2-R 1 -COOH as the first ligand to prepare a quantum dot film; or the second quantum dots are mixed with a mixed solution containing an ester hydrolysis catalyst, heated to cause the compound A on the surface of the second quantum dots to undergo an ester hydrolysis reaction to generate the first ligand, thereby obtaining second quantum dots with the first ligand bound to the surface, and a film is formed on the substrate to prepare a quantum dot film.
[0033] The method for preparing a quantum dot film provided by an embodiment of the present invention uses a ligand exchange method to first bind compound A on the surface of the quantum dot, and after film formation, the ester group of the ligand on the surface of the quantum dot layer is converted into a first ligand-a straight-chain organic carboxylic acid through a hydrolysis reaction. The quantum dot film thus obtained can improve its surface properties, thereby improving the contact performance with the adjacent layer material, and further improving the optical performance.
[0034] When the quantum dot film is used as the quantum dot light-emitting layer of the quantum dot light-emitting diode and contacts the metal compound in the electron transport layer, the straight-chain organic carboxylic acid after the hydrolysis of compound A combines with the metal ions to obtain a quantum dot surface of quantum dot-first ligand-metal ion, thereby forming a QDs / ETL interface containing metal ions with the metal compounds in the electron transport layer such as metal oxides, especially zinc oxide, so that the binding force between the quantum dots and the electron transport layer is enhanced, the contact angle is reduced, and a mixed phase interface or an interface with very small intrinsic tension is formed, which is conducive to the injection of electrons from the electron transport layer into the quantum dots, reduces the charge accumulation at the QD / ZnO interface and the device damage and attenuation caused by stress, so that the device service life and luminous efficiency are improved, which is of great significance for realizing a high-quality and strong-binding multilayer film structure.
[0035] Specifically, in the above step S01, a compound A to be reacted and a first quantum dot are provided under an inert atmosphere. The inert atmosphere refers to an inert gas atmosphere or a vacuum atmosphere; the first quantum dot refers to a quantum dot having a ligand to be exchanged on the surface. The quantum dot material in the first quantum dot (excluding surface ligands) can be a core structure or a core-shell structure. In some embodiments, the core compound and shell compound of the quantum dot matrix can be individually selected from but not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, H gZnSeS, HgZnSeTe, HgZnSTe; or III-V GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb , GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb; or IV-VI group SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; or any one or more combinations of the above.
[0036] In the embodiment of the present application, in compound A, X 1 is the first active group combined with the first quantum dot; R 1 -(CH2) n -, R 2 For straight chain C m H 2m+1, m and n are positive integers, and the value range of n+m is 2 to 12. In this case, compound A can replace the surface ligand of the first quantum dot under the first heating condition, and bind to the surface of the quantum dot through the first active group to obtain a second quantum dot with compound A bound to the surface.
[0037] Specifically, in compound A, the ester group can be hydrolyzed in the following step S02 to obtain a first ligand containing a carboxyl group; the value of s+m satisfies the range of 2 to 12. In this case, the carbon atom length of compound A is suitable, so that it has less steric hindrance and better solubility, which reduces the difficulty of introducing compound A into the surface of quantum dots. In some embodiments, the first active group is selected from one of carboxyl, hydroxyl, amino, thiol, and nitro, preferably carboxyl. In some embodiments, compound A is selected from at least one of monomethyl suberate, monoethyl pimelate, and monoethyl azelaic acid.
[0038] In some embodiments, the step of providing a mixed solution system of a fatty acid solution of compound A and a first quantum dot comprises: separately configuring a fatty acid solution of compound A and a non-polar solution of the first quantum dot, mixing and treating to obtain a mixed solution system. Among them, the non-polar solution of the first quantum dot is obtained by dispersing the quantum dots in a non-polar solvent. The use of a non-polar solvent can improve the dispersibility of the first quantum dots, and can prevent the first quantum dots from agglomerating and precipitating in a polar solvent, affecting the ligand exchange on the surface of the quantum dots. In the fatty acid solution of compound A, fatty acid, as a solvent for compound A, provides a good dissolution state for compound A to participate in the ligand exchange reaction; more importantly, since the initial quantum dot solution uses a non-polar solvent, the addition of fatty acids can improve the wetting and penetration of compound A in the initial quantum dot solution, so as to enhance the affinity and solubility of compound A to the initial quantum dot solution, so as to promote the ligand exchange reaction. In some embodiments, the fatty acid in the fatty acid solution of compound A is selected from at least one of n-octanoic acid, acetic acid, n-hexanoic acid, n-butyric acid, and n-pentanoic acid.
[0039] In some embodiments, in the mixed solution system of the fatty acid solution of compound A and the first quantum dots, the molar ratio of compound A to the first quantum dots is 50 to 100:1, so that the surface ligands of compound A and the first quantum dots are fully exchanged to obtain the first quantum dots with the surface bound to compound A. If the relative content of compound A is too high, higher than 100:1, the polarity of the quantum dots is significantly increased due to too many ligands, resulting in easy precipitation of the quantum dots.
[0040] In some embodiments, in the step of performing a ligand exchange reaction under a first heating condition, the temperature of the first heating condition is 100°C to 200°C, and the time of the ligand exchange reaction is 20min to 40min. If the temperature of the first heating condition is too low or the reaction time is too short, the difficulty of exchanging the surface ligands of the initial quantum dots increases, and even the ligand exchange reaction cannot effectively occur. If the temperature of the first heating condition is too high or the reaction time is too long, on the one hand, miscellaneous side reactions are likely to occur, affecting the effect of quantum dot ligand exchange, and introducing impurities that are difficult to remove into the quantum dots; on the other hand, too high a temperature will reduce the activity of the exchange reaction and affect the effect of ligand exchange. In addition, too high a temperature can easily lead to the volatilization of fatty acids, which is not conducive to the contact between compound A and the first quantum dot, and increases the difficulty of ligand exchange between the first quantum dot and compound A.
[0041] In some embodiments, after the step of performing a ligand exchange reaction under the first heating condition, the method further includes: dispersing the obtained reaction system in a polar solvent, collecting quantum dot precipitates; and dissolving the obtained quantum dots in a non-polar solvent, and repeating the process at least once.
[0042] In the first implementation based on the above embodiment, the first quantum dot is a quantum dot having an initial ligand on its surface, and the surface of the second quantum dot is only bound to compound A. The initial ligand is usually a surface ligand introduced when preparing the quantum dot, usually an oily ligand such as oleic acid. In this case, the initial ligand on the surface of the first quantum dot can be replaced with compound A by performing a ligand exchange reaction under the first heating condition. Specifically, compound A is bound to the surface of the first quantum dot through the first active group to form a second quantum dot with compound A bound to its surface.
[0043] In a second implementation based on the above embodiment, the second quantum dot is a quantum dot comprising compound A and a second ligand at the same time, wherein the second ligand is a compound having at least two benzene rings, and the second ligand contains a second active group that is bound to the quantum dot particle, and the polarity of the second active group is stronger than that of the first active group. On the one hand, the polybenzene ring structure containing the second active group, in which the conjugated structure has a strong affinity with the hole transport layer, can promote the injection of holes in the hole transport layer into the quantum dot; at the same time, due to the large polarity of the second active group, after coordination with the quantum dot, the second active group is connected to the quantum dot, so that the surface electrons of the quantum dot are enriched, and a strong negative potential is formed on the surface of the quantum dot, and the negative potential forms an electric field with the positive potential of the hole transport layer material surface, further promoting the hole from the hole transport layer into the quantum dot light-emitting layer, which is equivalent to the strong electron-withdrawing conjugation effect of the second ligand to simultaneously move up the rewinding energy level and the valence band energy level of the quantum dot shell, changing the shell energy level of the quantum dot and promoting the migration of holes. On the other hand, after the quantum dots combined with compound A are formed into a film, the straight-chain organic carboxylic acid produced by the hydrolysis of compound A changes the functional groups on the surface of the quantum dot film after hydrolysis, converting the ester group of compound A on the surface into a carboxyl group. The carboxylic acid functional groups on the surface are coordinated and connected with the metal oxide materials of the electron transport layer, such as ZnO, which greatly enhances the interface binding force of QDs / ETL and weakens the interface stress. The interface stress has a great influence on the electronic cloud structure of the interface. Weakening the interface stress is conducive to the conduction of electrons at the QDs / ETL interface. At the same time, the energy level of the QDs / ETL interface remains basically unchanged, and the energy level position of the quantum dot conduction band does not move up. In summary, the ability of the electron transport layer (ETL) to inject electrons into QDs is still strong, and finally a quantum dot film with a gradient energy level is formed, which improves the charge balance ability of the device and improves the luminous efficiency and service life of the device.
[0044] In some embodiments, the second active group is selected from one of a nitro group, a sulfonic acid group and a trihalomethyl group, and the halogen atom in the trihalomethyl group is selected from one of fluorine, chlorine and bromine. The above-mentioned strong electron-withdrawing group enriches the surface electrons of the second quantum dot after binding to the second ligand, and forms a strong negative potential on the surface of the quantum dot, which forms an electric field with the positive potential on the surface of the hole transport layer material, further promoting the holes from the hole transport layer to enter the quantum dot light-emitting layer.
[0045] In some embodiments, the second ligand is selected from at least one of a condensed ring having 2 to 6 benzene rings, biphenyl, and a hyperconjugated structure containing -Ar-C=C-Ar-, wherein Ar is a benzene ring. In the hyperconjugated structure containing -Ar-C=C-Ar-, the position of the second active group is not strictly limited, and can be combined on the benzene ring or on the double bond carbon atom.
[0046] In some embodiments, the second ligand is selected from one of the compounds shown in Formula 1 and Formula 2, wherein R3 is selected from one of a hydrogen atom, a benzene ring, and an olefin, X 2 is a second active group combined with the second quantum dot; and the second active group is selected from one of a nitro group, a sulfonic acid group and a trihalomethyl group, and the halogen atom in the trihalomethyl group is selected from one of fluorine, chlorine and bromine
[0047]
[0048] In some embodiments, the second quantum dot is a quantum dot containing compound A and a second ligand at the same time, and after the ligand exchange reaction is performed under the first heating condition, it also includes: under an inert atmosphere, adding a second ligand to the reaction system with the second quantum dot of compound A bound to the surface, and performing a ligand exchange reaction under the second heating condition to prepare a second quantum dot with compound A and the second ligand bound to the surface at the same time. Specifically, under an inert atmosphere, a fatty acid solution of the second ligand is added to the reaction system, and the fatty acid can improve the wetting and penetration of the second ligand in the quantum dot solution to enhance the affinity and solubility of the second ligand to the quantum dot solution, so as to promote the ligand exchange reaction. In some embodiments, the fatty acid in the fatty acid solution of the second ligand is selected from at least one of n-octanoic acid, acetic acid, n-hexanoic acid, n-butyric acid, and n-pentanoic acid.
[0049] In some embodiments, in the step of adding a second ligand to a reaction system having second quantum dots bound to the surface of compound A, the second ligand is added to the reaction system having second quantum dots bound to the surface of compound A at a molar ratio of the second ligand to the first quantum dots of 0.5 to 4:1. At this time, the molar ratio of compound A to the second ligand on the surface of the obtained second quantum dots is approximately 1:1.
[0050] In some embodiments, in the step of performing a ligand exchange reaction under the first heating condition, the temperature of the first heating condition is 100°C to 150°C, and the time of the exchange reaction is 2h to 4h. On this basis, in the step of performing a ligand exchange reaction under the second heating condition, the temperature of the second heating condition is 80°C to 100°C, and the time of the exchange reaction is 8h to 16h. If the temperature of the second heating condition is too low or the reaction time is too short, it is difficult to effectively exchange the compound A of the first quantum dot, and even the ligand exchange reaction cannot effectively occur. If the temperature of the first heating condition is too high or the reaction time is too long, on the one hand, miscellaneous side reactions are prone to occur, affecting the effect of quantum dot ligand exchange, and introducing impurities that are difficult to remove into the quantum dots; on the other hand, too high a temperature will reduce the activity of the exchange reaction and affect the effect of ligand exchange. In addition, too high a temperature can easily lead to the volatilization of fatty acids, which is not conducive to the contact between the second ligand and the quantum dot, and increases the difficulty of ligand exchange between the first quantum dot and the second ligand.
[0051] In some embodiments, after the step of performing a ligand exchange reaction under the second heating condition, the method further includes: dispersing the obtained reaction system in a polar solvent, collecting quantum dot precipitates; and dissolving the obtained quantum dots in a non-polar solvent, and repeating the process at least once.
[0052] In some embodiments, compound A is monomethyl suberate, and the second ligand is 9-nitroanthracene, that is, the second quantum dot surface is simultaneously bound to two ligands, 9-nitroanthracene and monomethyl suberate. Figure 2 As shown, after the non-polar solvent of the first quantum dots whose initial ligand is oleic acid is mixed with the fatty acid solution of monomethyl suberate, under the first heating condition, the monomethyl suberate replaces the original ligand on the surface of the first quantum dots to obtain a second quantum dot solution with monomethyl suberate as the ligand; as shown Figure 3 As shown, a fatty acid solution of 9-nitroanthracene is added to the first quantum dot solution. Under the second heating condition, the strong electron-withdrawing group on 9-nitroanthracene is similar to halogen, and the lone electron pair of the oxygen atom on the group is easy to coordinate with the second quantum dot to replace the monomethyl suberate, that is, 9-nitroanthracene replaces the monomethyl suberate on the surface of the second quantum dot, and the second quantum dot with both 9-nitroanthracene and monomethyl suberate combined on the surface is obtained. Figure 4 As shown, after 9-nitroanthracene is coordinated with quantum dots, the nitro group is connected to the quantum dots. The nitro group is a strong electron-withdrawing group. The quantum dots themselves are n-type semiconductors. Therefore, the nitro group can enrich the electrons on the surface of the quantum dots and form a strong negative potential on the surface of the quantum dots. This negative potential forms an electric field with the positive potential on the surface of the HTL material, promoting the injection of holes from the HTL layer into the quantum dots. This is equivalent to the strong electron-withdrawing conjugation effect of 9-nitroanthracene. The conduction band energy level and the valence band energy level of the quantum dot shell are simultaneously moved up, changing the shell energy level of the quantum dots. Since the polyphenyl ring structure of 9-nitroanthracene has a strong affinity with TFB, the QDs / HTL interface side is a 9-nitroanthracene ligand. At the same time, the use of suberic acid monoester changes the functional groups on the surface of the quantum dot film after the quantum dot film is formed due to the hydrolysis reaction. The ester group of monomethyl suberate on the surface of the quantum dot film is converted into a carboxyl group. The carboxylic acid functional group on the upper surface is coordinated and connected with the metal oxide of the electron transport layer such as ZnO, which greatly enhances the interface binding force of QDs / ETL and weakens the interface stress. The interface stress has a great influence on the electronic cloud structure of the interface. Reducing the interface stress is beneficial to the conduction of electrons at the QDs / ETL interface. At the same time, the QDs / ETL interface energy level remains basically unchanged, and the quantum dot conduction band energy level position does not move up. Therefore, the ability of ETL to inject electrons into QDs is still strong, and finally a quantum dot film with gradient energy levels is formed, which improves the charge balance ability of the device and improves the efficiency and life of the device.
[0053] In a third implementation based on the above embodiment, the second quantum dot is a quantum dot comprising both compound A and a third ligand, wherein the third ligand is a compound having a general structural formula as shown in Formula 3; wherein R 4 A substituent selected from a group having 1 to 6 carbon atoms and a terminal containing a third active group that is bound to the second quantum dot, wherein the polarity of the third active group is stronger than that of the first active group; and the third ligands are cross-linked through a polymerization reaction of double bonds to form a network structure;
[0054] In this case, a compound with a general structure as shown in Formula 3 is used as the third ligand, and the third ligands of different quantum dots are connected through a polymerization reaction during the surface modification process, thereby connecting the quantum dots in the same layer, shortening the spacing between the quantum dots in the same layer, and at the same time, the quantum dots between different layers are also connected, thereby shortening the spacing between the quantum dots between the layers, polymerizing to form a chain polymer, and the quantum dots are arranged in an orderly manner, and are tightly connected through the ligands to form a preferred orientation, providing a basic skeleton for the crystallization of the quantum dot layer. Due to the shortened spacing between quantum dots, the charge transfer of the interlayer quantum dots and the charge transfer of the quantum dots within the layer are both enhanced, and the chain polymer forms a lamellar crystal through the folding and rotation of the molecules during the heating process, so that the quantum dot superlattice structure is also a lamellar superlattice structure, which has good planar two-dimensional conductivity, that is, the quantum dot film has good conductivity within the plane. At the same time, the quantum dot layers can be connected by straight-chain organic carboxylic acids containing the first active group to form a QDs-first ligand-QDs structure, and the formed flake crystals can be connected and stacked to form layered crystals. This layered crystal structure has a strong carrier transmission ability between quantum dots. The QDs-first ligand-QDs structure can act as a charge transfer center, and its longitudinal conductivity is better than that of flake crystals, thereby improving the electrical conductivity of the quantum dot film. Since the straight-chain organic carboxylic acid containing the first active group has a strong affinity with the transport layer, when the quantum dot film is used as the light-emitting layer of the quantum dot light-emitting diode, the contact surface between the quantum dot film and the transport layer is the straight-chain organic carboxylic acid containing the first active group, and the QDs / ETL interface is mainly composed of the straight-chain organic carboxylic acid containing the first active group. The quantum dots on the interface can be connected to the electron transport material such as ZnO through the straight-chain organic carboxylic acid containing the first active group to form an electron transport material-first ligand-QDs structure, which modifies the QDs / ETL interface, reduces the contact angle of spin coating, improves the film quality of the electron transport material, enhances the transmission capacity of interface electrons, makes it easier for electrons to be injected from the electron transport material into the quantum dots, and improves the luminous efficiency and service life of the quantum dot light-emitting device.
[0055] In some embodiments, the third reactive group is selected from one of hydroxyl, carboxyl, thiol, amino, and nitro, preferably hydroxyl, and the polarity of the third reactive group is stronger than that of the first reactive group.
[0056] In some embodiments, the third ligand is selected from at least one of hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate.
[0057] In some embodiments, the second quantum dot is a quantum dot containing both compound A and a third ligand, and after the ligand exchange reaction is performed under the first heating condition, the method further comprises: adding a third ligand to the reaction system of the second quantum dot having compound A bound to the surface under an inert atmosphere, and performing a ligand exchange reaction under a third heating condition to prepare a second quantum dot having compound A and the third ligand bound to the surface at the same time;
[0058] After the step of preparing the second quantum dot whose surface contains both compound A and the third ligand, the method further includes: adding a mixed solution containing an initiator and a crosslinking agent into the second quantum dot, and heating to cause the third ligand on the surface of the second quantum dot to undergo a polymerization reaction.
[0059] In some embodiments, under an inert atmosphere, the step of adding a third ligand to the obtained reaction system includes: respectively configuring a non-polar solution of the second quantum dots of compound A and a fatty acid solution of the third ligand, and mixing the two. Wherein, the non-polar solution of the second quantum dots of compound A is obtained by dispersing the second quantum dots in a non-polar solvent. The use of a non-polar solvent can improve the dispersibility of the quantum dots, and can prevent the quantum dots from agglomerating and precipitating in a polar solvent, affecting the ligand exchange on the surface of the quantum dots. In the fatty acid solution of the third ligand, the fatty acid, as a solvent for the third ligand, provides a good dissolution state for the third ligand to participate in the reaction; more importantly, since the second quantum dot solution uses a non-polar solvent, the addition of fatty acids can improve the infiltration and penetration of the third ligand in the quantum dot solution, so as to enhance the affinity and solubility of the third ligand to the quantum dot solution, so as to promote the ligand exchange reaction. In some embodiments, the fatty acid in the fatty acid solution of the first ligand is selected from at least one of n-octanoic acid, acetic acid, n-hexanoic acid, n-butyric acid, and n-pentanoic acid.
[0060] In some embodiments, a non-polar solution of the second quantum dots of compound A and a fatty acid solution of the third ligand are separately prepared and mixed, and in the step of mixing the two, a molar ratio of the third ligand to the second quantum dots of compound A is 50 to 100:1.
[0061] In some embodiments, a ligand exchange reaction is performed under the third heating condition, and part of the compound A on the surface of the second quantum dot can be replaced by the third ligand. Specifically, the third ligand is bound to the surface of the quantum dot through the third active group to form a second quantum dot with the third ligand and compound A bound to the surface.
[0062] In some embodiments, in the step of performing a ligand exchange reaction under the first heating condition, the temperature of the first heating condition is 100°C to 200°C, and the time of the exchange reaction is 2h to 4h. On this basis, in the step of performing a ligand exchange reaction under the third heating condition, the temperature of the third heating condition is 60°C to 90°C, and the time of the exchange reaction is 4h to 16h. If the temperature of the third heating condition is too low or the reaction time is too short, it is difficult to effectively exchange the surface ligand compound A of the second quantum dot, and even the ligand exchange reaction cannot effectively occur. If the temperature of the third heating condition is too high or the reaction time is too long, on the one hand, miscellaneous side reactions are prone to occur, affecting the effect of quantum dot ligand exchange, and introducing impurities that are difficult to remove into the quantum dots; on the other hand, too high a temperature will reduce the activity of the exchange reaction and affect the effect of ligand exchange. In addition, too high a temperature can easily lead to the volatilization of fatty acids, which is not conducive to the contact between the third ligand and the second quantum dot, and increases the difficulty of ligand exchange between the second quantum dot and the third ligand.
[0063] In some embodiments, after the step of performing a ligand exchange reaction under the third heating condition, the step further includes: dispersing the obtained reaction system in a polar solvent, collecting quantum dot precipitates; and dissolving the obtained quantum dots in a non-polar solvent, and repeating the process at least once.
[0064] In some embodiments, compound A is monomethyl suberate, and the third ligand is 2-hydroxyethyl methacrylate (HEMA), that is, the surface of the quantum dots in the quantum dot film is simultaneously bound to two ligands, suberic acid and HEMA. Under an inert gas atmosphere, a mixed solution of a non-polar solvent of the first quantum dots with oleic acid as the initial ligand and a fatty acid solution of monomethyl suberate is heated under a first condition to obtain a first quantum dot solution with monomethyl suberate as a ligand. A small amount of a mixture of fatty acids and ethanol is then added, and the mixture is hydrolyzed at 60-80°C for 2 hours to obtain a second quantum dot solution with suberic acid as the main ligand. HEMA is added to the second quantum dot solution, and ligand exchange is carried out under a second heating condition for 4-16 hours to obtain a second quantum dot solution with suberic acid and HEMA as ligands. Figure 5As shown in the figure, HEMA is used as the third ligand, and the third ligands on the surfaces of different quantum dots are connected through the polymerization reaction between the ligands, thereby connecting the quantum dots in the same layer, shortening the distance between the quantum dots in the same layer. On the other hand, it can be seen from the double bond bonding path shown in the figure that the quantum dots in different layers are also connected, thereby shortening the distance between the quantum dots between the layers and polymerizing to form a chain polymer. The quantum dots are arranged in an orderly manner as shown in the figure, and are closely connected by the ligands to form a preferred orientation, providing a basic skeleton for the crystallization of the quantum dot layer. Due to the shortened distance between the quantum dots, the charge transport of the interlayer quantum dots and the charge transport of the quantum dots within the layer are enhanced. The chain polymer forms a lamellar crystal through the folding and rotation of the molecules during the heat treatment process such as 100°C after the metal oxide material such as ZnO of the electron transport layer is spin-coated. At the same time, the quantum dot layers can also be connected by suberic acid to form a QDs-first ligand-QDs structure, and the formed flake crystals are connected and stacked to form layered crystals. This layered crystal structure has a strong carrier transmission capacity between quantum dots. The QDs-first ligand-QDs structure can act as a charge transmission center, and the longitudinal conductivity is better than that of flake crystals, which improves the conductivity of the quantum dot film. Since suberic acid has a strong affinity with the transport layer, the contact surface between the quantum dot film and the transport layer is a suberic acid ligand, and the QDs / ETL interface is mainly suberic acid. The quantum dots on the interface can be connected to ZnO through suberic acid to form an electron transport material-first ligand-QDs structure, which modifies the QDs / ETL interface, reduces the contact angle of spin coating, improves the film quality of zinc oxide, and enhances the transmission capacity of interface electrons, making it easier for electrons to be injected from the electron transport layer into the quantum dots, thereby improving the luminous efficiency and service life of quantum dot light-emitting diode devices.
[0065] In the fourth embodiment based on the above embodiment, the second quantum dot is a quantum dot comprising compound A and a fourth ligand at the same time, wherein the fourth ligand is a MOF monomer, and the MOF monomer contains at least three fourth active groups combined with the quantum dot, and the polarity of the fourth active group is stronger than the polarity of the first active group. MOF monomer is an organic monomer material for forming MOF (metal-organic framework material). MOF monomer is combined with the surface of quantum dot. On the one hand, MOF monomer has self-assembly characteristics. Therefore, in the process of quantum dot film formation, driven by MOF monomer, the surface is combined with MOF quantum dots in an orderly manner, which improves the film forming processability and uniform order of quantum dots. On the other hand, a quantum dot surface is combined with multiple MOF monomers at the same time to form a skeleton structure similar to MOF, which can reduce the surface defects of quantum dots. At the same time, the micropores between MOF monomers in the skeleton structure similar to MOF are filled by quantum dots, thereby improving the crystallinity of quantum dot film and obtaining a high-quality superlattice quantum dot structure. Two aspects act simultaneously to eventually form an ordered high-quality superlattice structure (similar to the skeleton structure of MOF). In this case, the ordered high-quality superlattice structure can solve the problem of many defects in quantum dot films and loose and disordered structures, effectively improve the transmission capacity of carriers, improve the conductivity of quantum dot films, and then when the quantum dot material is used as the light-emitting layer material of quantum dot light-emitting diodes, it can enhance the ability of excitons to recombine in the light-emitting layer, reduce the charge accumulation at the interface between the quantum dot light-emitting layer and the electron transport layer, solve the problem of device charge imbalance caused by the hole mobility being much lower than the electron mobility, and finally improve the service life and luminous efficiency of quantum dot light-emitting devices. Furthermore, since the first ligand contains more than three first active groups at the same time, a MOF monomer can simultaneously connect multiple quantum fixed particles, thereby shortening the distance between quantum dots, reducing the electron transmission distance between quantum dots, and further improving the carrier migration ability of quantum dots. In addition, the quantum dot film provided by the embodiment of the present application has a large steric hindrance of the MOF monomer on the surface of the quantum dot, which can prevent agglomeration between quantum dots, thereby improving its film processing performance. On this basis, straight-chain organic carboxylic acid ligands are used to fill the gaps in MOF monomers to form a QDs-first ligand-QDs structure, and QDs-first ligand-QDs are used to extend outward in a chain to fill the gaps in the three-dimensional skeleton and surround the three-dimensional longitudinal skeleton to form a transverse structure. The grain size formed in this way is large, and it is a large grain structure with ultra-long-range carrier conduction capability, which increases the maximum diffusion length of carriers, improves the carrier transmission capacity of the quantum dot film, reduces the number of grain boundaries and the corresponding number of defects, and improves the luminescence efficiency and service life of the device.
[0066] In some embodiments, the fourth active group is selected from a hydroxyl group, a carboxyl group, a thiol group, and an amino group. The fourth active groups in the same MOF monomer may be the same or different.
[0067] In some embodiments, the fourth ligand is selected from the compound shown in the following formula 4, wherein X 4 , X 5 , X 6 is the same or different fourth active group:
[0068]
[0069] The compound shown in Formula 4 contains three fourth active groups that bind to quantum dots. The three fourth active groups can bind to three quantum dots, thereby weaving the quantum dot particles into a network structure to form a stable and orderly superlattice structure. The ligand structure on the surface of the quantum dots has a high degree of conjugation. Therefore, using the compound shown in Formula 4 as the surface ligand of the quantum dots can further improve the carrier transport performance of the quantum dots by means of the conjugation effect.
[0070] In some embodiments, the second quantum dot is a quantum dot that simultaneously contains compound A and a fourth ligand, and after performing a ligand exchange reaction under a first heating condition, it also includes: under an inert atmosphere, adding a fourth ligand to the obtained reaction system, performing a ligand exchange reaction under a fourth heating condition, and preparing a second quantum dot having compound A and a fourth ligand simultaneously bound to the surface.
[0071] In some embodiments, under an inert atmosphere, the step of adding a fourth ligand to the obtained reaction system includes: respectively configuring a non-polar solution of the second quantum dots of compound A and a fatty acid solution of the fourth ligand, and mixing the two. Among them, the non-polar solution of the second quantum dots of compound A is obtained by dispersing the second quantum dots in a non-polar solvent. The use of a non-polar solvent can improve the dispersibility of the quantum dots, and can prevent the quantum dots from agglomerating and precipitating in a polar solvent, affecting the ligand exchange on the surface of the quantum dots. In the fatty acid solution of the fourth ligand, the fatty acid, as a solvent for the fourth ligand, provides a good dissolution state for the fourth ligand to participate in the reaction; more importantly, since the second quantum dot solution uses a non-polar solvent, the addition of fatty acids can improve the infiltration and penetration of the fourth ligand in the quantum dot solution, so as to enhance the affinity and solubility of the fourth ligand to the quantum dot solution, so as to promote the ligand exchange reaction. In some embodiments, the fatty acid in the fatty acid solution of the first ligand is selected from at least one of n-octanoic acid, acetic acid, n-hexanoic acid, n-butyric acid, and n-pentanoic acid.
[0072] In some embodiments, in the step of separately preparing a non-polar solution of the second quantum dots of compound A and a fatty acid solution of the fourth ligand and mixing the two, the molar ratio of the fourth ligand to the second quantum dots of compound A is 1 to 5:1.
[0073] In some embodiments, a ligand exchange reaction is performed under the fourth heating condition, and part of the compound A on the surface of the second quantum dot can be replaced with the fourth ligand. Specifically, the fourth ligand is bound to the surface of the quantum dot through the fourth active group to form a second quantum dot with the fourth ligand and compound A bound to the surface.
[0074] In some embodiments, in the step of performing a ligand exchange reaction under the first heating condition, the temperature of the first heating condition is 100°C to 150°C, and the time of the exchange reaction is 1h to 2h. On this basis, in the step of performing a ligand exchange reaction under the fourth heating condition, the temperature of the fourth heating condition is 100°C to 200°C, and the time of the exchange reaction is 8h to 16h. If the temperature of the fourth heating condition is too low or the reaction time is too short, it is difficult to effectively exchange the surface ligand compound A of the second quantum dot, and even the ligand exchange reaction cannot effectively occur. If the temperature of the fourth heating condition is too high or the reaction time is too long, on the one hand, miscellaneous side reactions are prone to occur, affecting the effect of quantum dot ligand exchange, and introducing impurities that are difficult to remove into the quantum dots; on the other hand, too high a temperature will reduce the activity of the exchange reaction and affect the effect of ligand exchange. In addition, too high a temperature can easily lead to the volatilization of fatty acids, which is not conducive to the contact between the fourth ligand and the second quantum dot, and increases the difficulty of ligand exchange between the second quantum dot and the fourth ligand.
[0075] In some embodiments, after the step of performing a ligand exchange reaction under the fourth heating condition, the step further includes: dispersing the obtained reaction system in a polar solvent, collecting quantum dot precipitates; and dissolving the obtained quantum dots in a non-polar solvent, and repeating the process at least once.
[0076] In some embodiments, compound A is monomethyl suberate, and the fourth ligand is 1,3,5-tri(4-carboxyphenyl)benzene. That is, compound A and the fourth ligand are simultaneously bound to the surface of the second quantum dot. Under an inert gas atmosphere, a fatty acid solution of monomethyl suberate is added to the non-polar solvent of the first quantum dot, and the temperature is raised to 100-150°C for ligand exchange for 1-2 hours to obtain a second quantum dot solution with suberic acid as a ligand. Then, a small amount of a mixture of fatty acids and ethanol is added, and the mixture is hydrolyzed at 100-150°C for 4-8 hours to obtain a second quantum dot solution with suberic acid as a ligand. Under an inert gas atmosphere, a fatty acid solution of 1,3,5-tri(4-carboxyphenyl)benzene is added to the second quantum dot solution, and the temperature is raised to 100-200°C, and ligand exchange is performed for 8-16 hours to obtain a second quantum dot solution with 1,3,5-tri(4-carboxyphenyl)benzene and suberic acid as ligands. As Figure 6As shown, 1,3,5-tri(4-carboxyphenyl)benzene and suberic acid are used as ligands, and the three-coordination site self-assembly property of 1,3,5-tri(4-carboxyphenyl)benzene forms a large MOF-like superlattice skeleton. As shown in the figure, a single MOF is coordinated with three quantum dots, and a quantum dot has multiple ligands covering all the dangling bonds on the surface of the quantum dot. All quantum dots are connected by the connecting effect of MOF monomers to form a large three-dimensional structure. Such a three-dimensional structure has good longitudinal conductivity because the longitudinal direction is composed of a MOF-like skeleton. However, such a three-dimensional structure has many gaps and micropores. When using suberic acid ligands, the gaps formed are filled by suberic acid to form a QDs-first ligand-QDs structure, and QDs-first ligand-QDs are used to extend outward in a chain to fill the gaps in the three-dimensional skeleton and surround the three-dimensional longitudinal skeleton to form a transverse structure. The grain size formed in this way is large, and it is a large grain structure with ultra-long-range carrier conduction capability, which increases the maximum diffusion length of carriers, improves the carrier transmission capacity of the quantum dot film, reduces the number of grain boundaries and the corresponding number of defects, and improves the luminescence efficiency and life of the device.
[0077] In the above step S02, in one embodiment, a substrate is provided, and second quantum dots are deposited on the substrate to prepare a quantum dot prefabricated film. Depositing the second quantum dots on the substrate to prepare the quantum dot prefabricated film can be achieved by solution processing, including but not limited to spin coating, inkjet printing, scraping, etc.
[0078] In an embodiment of the present application, a mixed solution containing an ester hydrolysis catalyst is deposited on a quantum dot prefabricated film, and heating is performed to cause at least compound A on the surface of the quantum dot prefabricated film to undergo an ester hydrolysis reaction to generate a first ligand, thereby preparing a quantum dot film. In some embodiments, the ester hydrolysis catalyst is selected from an aqueous alcohol solution of an alkali.
[0079] In some embodiments, the substrate is a substrate having an electron transport material on its surface, and in the step of depositing a mixed solution containing an ester hydrolysis catalyst on the quantum dot prefabricated film, the mixed solution containing the ester hydrolysis catalyst also contains a metal precursor; and in the step of heating to hydrolyze the compound A at least on the surface of the quantum dot prefabricated film to form a first ligand, the first ligand is combined with the metal in the metal precursor to form a quantum dot-first ligand-metal structure. In this case, the compound A on the surface of the quantum dot at the interface between the quantum dot prefabricated film and the substrate undergoes an ester hydrolysis reaction to generate the first ligand, and the carboxyl group on the first ligand is combined with the metal ion in the metal precursor to obtain a quantum dot surface with a QDs-first ligand-metal ion structure. On this basis, the QDs-first ligand-metal ion structure on the surface of the quantum dots and the metal oxide material of the electron transport layer, such as zinc oxide, form a QDs / ETL interface containing metal ions, further enhancing the binding force between the quantum dots and the electron transport layer. The contact angle becomes smaller, forming a mixed phase interface or an interface with very small intrinsic tension, which is beneficial to the injection of electrons from the HTL into the quantum dots, reducing the charge accumulation at the QD / ZnO interface and the device damage and attenuation caused by stress, thereby improving the device life and efficiency, which is of great significance for realizing high-quality and strong-binding multilayer film structures.
[0080] In some embodiments, the electron transport material is a metal compound nanoparticle, and the metal in the metal precursor is the same as the metal in the electron transport material. In this case, the binding force between the QDs-first ligand-metal ion structure on the surface of the quantum dots and the electron transport layer is further enhanced.
[0081] In some embodiments, the electron transport material is zinc oxide nanoparticles, and the metal precursor is selected from at least one of zinc acetate, diethyl zinc, zinc chloride, zinc bromide, zinc iodide, and zinc stearate.
[0082] In another embodiment, the second quantum dot is mixed with a mixed solution containing an ester hydrolysis catalyst, and heated to cause the compound A on the surface of the second quantum dot to undergo an ester hydrolysis reaction to generate a first ligand, thereby obtaining a second quantum dot with the first ligand bound to the surface, and a film is formed on the substrate to prepare a quantum dot film. The types of ester hydrolysis catalysts are as described above, and are not described here in detail to save space.
[0083] It is worth noting that in the embodiments of the present application, the non-polar solvent used can be selected from n-hexane, n-octane, and chlorobenzene, but not limited thereto; the polar solvent used can be selected from any one of anhydrous ethanol, ethyl acetate, acetone, chloroform, and methanol, but not limited thereto.
[0084] A second aspect of an embodiment of the present invention provides a quantum dot film, the quantum dot film is composed of quantum dots, the quantum dots include a quantum dot matrix, a first ligand bound to the surface of the quantum dot matrix, and at least one of a second ligand, a third ligand, and a fourth ligand bound to the surface of the quantum dot matrix, wherein the first ligand is X 1 -CH2-R 1 -COOH, X 1 is the first active group combined with the quantum dot matrix; R 1 -(CH2) n -, n is a positive integer, and the value of n is in the range of 1 to 10.
[0085] The quantum dot film provided in the embodiment of the present invention is composed of quantum dots, and the surface of the quantum dots is at least combined with a general structure of X 1 -CH2-R 1 The quantum dot film provided by the method can improve its surface properties, thereby improving the contact performance with the adjacent layer materials and further improving the optical performance.
[0086] When the quantum dot film is used as the light-emitting layer of a quantum dot light-emitting diode, the first ligand on the quantum dots on the surface of the quantum dot film combines with the metal oxide in the electron transport layer to form a QDs / ETL interface containing metal ions, thereby enhancing the binding force between the quantum dots and the electron transport layer and reducing the contact angle, forming a mixed phase interface or an interface with very small intrinsic tension, which is beneficial to the injection of electrons from the electron transport layer into the quantum dots, reducing the charge accumulation at the QD / ZnO interface and the device damage and attenuation caused by stress, thereby improving the device service life and luminous efficiency.
[0087] In the embodiments of the present application, the quantum dot matrix refers to a quantum dot material that does not contain ligands on the surface. The quantum dot material can be a core structure or a core-shell structure. In some embodiments, the core compound and shell compound of the quantum dot matrix can be individually selected from but not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, H gZnSeS, HgZnSeTe, HgZnSTe; or III-V GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb , GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb; or IV-VI group SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; or any one or more combinations of the above.
[0088] In addition to the base quantum dot material forming the quantum dot film, the quantum dot film also includes ligands bound to the surface of the quantum dot base. The ligands on the surface of the quantum dot can usually reduce the surface defects of the quantum dot and improve the luminescence performance of the quantum dot. Different from the surface ligands on conventional quantum dots, in the embodiment of the present application, the quantum dot includes a quantum dot base and at least two ligands bound to the surface of the quantum dot base. Among them, the first ligand is X 1 CH2R 1 COOH, X 1 is the first active group combined with the first quantum dot; R 1 -(CH2) n-, n is a positive integer, and the value of n satisfies the range of 1 to 10. In some embodiments, the first active group is selected from one of carboxyl, hydroxyl, amino, sulfhydryl, and nitro, preferably carboxyl. In some embodiments, the first ligand is selected from at least one of suberic acid, pimelic acid, and azelaic acid.
[0089] In the first implementation based on the above embodiment, the surface of the quantum dot is simultaneously bound to the first ligand and the second ligand, the second ligand is a compound having at least two benzene rings, and the second ligand contains a second active group bound to the quantum dot particle. In this case, on the one hand, the polybenzene ring structure containing the second active group, in which the conjugated structure is strong with the hole transport layer, can promote the injection of holes in the hole transport layer into the quantum dot; at the same time, due to the large polarity of the second active group, after coordination with the quantum dot, the second active group is connected to the quantum dot, so that the surface electrons of the quantum dot are enriched, and a strong negative potential is formed on the surface of the quantum dot, and the negative potential forms an electric field with the positive potential of the hole transport layer material surface, further promoting the hole from the hole transport layer into the quantum dot light-emitting layer, which is equivalent to the strong electron-withdrawing conjugation effect of the second ligand to simultaneously move up the reversal energy level and the valence band energy level of the quantum dot shell, changing the shell energy level of the quantum dot and promoting the migration of holes. On the other hand, after the quantum dots combined with the first ligand are formed into a film, the carboxylic acid functional groups on the surface of the quantum dot film are coordinated with the metal oxide materials of the electron transport layer, such as ZnO, which greatly enhances the interface binding force of QDs / ETL and weakens the interface stress. The interface stress has a great influence on the electronic cloud structure of the interface. Weakening the interface stress is conducive to the conduction of electrons at the QDs / ETL interface. At the same time, the energy level of the QDs / ETL interface remains basically unchanged, and the position of the quantum dot conduction band energy level does not move up. In summary, the ability of ETL to inject electrons into QDs is still strong, and a quantum dot film with gradient energy levels is finally formed, which improves the charge balance ability of the device and improves the luminous efficiency and service life of the device.
[0090] In some embodiments, the second active group is selected from one of a nitro group, a sulfonic acid group and a trihalomethyl group, and the halogen atom in the trihalomethyl group is selected from one of fluorine, chlorine and bromine. The above-mentioned strong electron-withdrawing group enriches the surface electrons of the second quantum dot after binding to the second ligand, and forms a strong negative potential on the surface of the quantum dot, which forms an electric field with the positive potential on the surface of the hole transport layer material, further promoting the holes from the hole transport layer to enter the quantum dot light-emitting layer.
[0091] In some embodiments, the second ligand is selected from at least one of a condensed ring having 2 to 6 benzene rings, biphenyl, and a hyperconjugated structure containing -Ar-C=C-Ar-, wherein Ar is a benzene ring.
[0092] In some embodiments, the second ligand is selected from one of the compounds shown in Formula 1 and Formula 2, wherein R 3is selected from one of a hydrogen atom, a benzene ring, and an olefin, X 2 is a second active group combined with the second quantum dot; and the second active group is selected from one of a nitro group, a sulfonic acid group and a trihalomethyl group, and the halogen atom in the trihalomethyl group is selected from one of fluorine, chlorine and bromine
[0093]
[0094] In some embodiments, the first ligand is suberic acid, and the second ligand is 9-nitroanthracene, that is, the surface of the quantum dots in the quantum dot film is simultaneously bound to 9-nitroanthracene and suberic acid ligands. Figure 4 As shown, after 9-nitroanthracene is coordinated with quantum dots, the nitro group is connected to the quantum dots. The nitro group is a strong electron-withdrawing group. The quantum dots themselves are n-type semiconductors. Therefore, the nitro group can enrich the electrons on the surface of the quantum dots and form a strong negative potential on the surface of the quantum dots. This negative potential forms an electric field with the positive potential on the surface of the HTL material, promoting the injection of holes from the HTL layer into the quantum dots. This is equivalent to the strong electron-withdrawing conjugation effect of 9-nitroanthracene. The conduction band energy level and the valence band energy level of the quantum dot shell are simultaneously moved up, changing the shell energy level of the quantum dots. Since the polyphenyl ring structure of 9-nitroanthracene has a strong affinity with TFB, the QDs / HTL interface side is a 9-nitroanthracene ligand. At the same time, the carboxylic acid functional groups in the suberic acid on the surface of the quantum dot film are coordinated and connected with the metal oxides such as ZnO in the electron transport layer, which greatly enhances the interface bonding force of QDs / ETL and weakens the interface stress. The interface stress has a great influence on the electron cloud structure of the interface. Weakening the interface stress is beneficial to the conduction of electrons at the QDs / ETL interface. At the same time, the energy level of the QDs / ETL interface remains basically unchanged, and the energy level position of the quantum dot conduction band has not moved up. Therefore, the ability of ETL to inject electrons into QDs is still strong, and finally a quantum dot film with a gradient energy level is formed, which improves the charge balance ability of the device and improves the efficiency and life of the device.
[0095] In a second implementation based on the above embodiment, the surface of the quantum dot is simultaneously bound to a first ligand and a third ligand, wherein the third ligand is a compound having a general structural formula as shown in Formula 3; wherein R 4 A substituent selected from a group having 1 to 6 carbon atoms and a terminal containing a third active group capable of binding to a quantum dot, wherein the polarity of the third active group is stronger than that of the first active group; and the third ligands are cross-linked through a polymerization reaction of double bonds to form a network structure;
[0096] In this case, a compound with a general structural formula as shown in Formula 3 is used as the third ligand, and the third ligands of different quantum dots are connected through a polymerization reaction during the surface modification process, thereby connecting the quantum dots in the same layer, shortening the spacing between the quantum dots in the same layer, and at the same time, the quantum dots between different layers are also connected, thereby shortening the spacing between the quantum dots between the layers, polymerizing to form a chain polymer, and the quantum dots are arranged in an orderly manner, and are tightly connected through the ligands to form a preferred orientation, providing a basic framework for the crystallization of the quantum dot layer. Due to the shortened spacing between quantum dots, the charge transfer of interlayer quantum dots and the charge transfer of intralayer quantum dots are both enhanced, and the chain polymer forms a lamellar crystal through the folding and rotation of the molecules during the heating process, so that the quantum dot superlattice structure is also a lamellar superlattice structure, which has good planar two-dimensional conductivity, that is, the quantum dot film has good conductivity in the plane. At the same time, the quantum dot layers can be connected by straight-chain organic carboxylic acids containing the first active group to form a QDs-first ligand-QDs structure, and the formed flake crystals can be connected and stacked to form layered crystals. This layered crystal structure has a strong carrier transmission ability between quantum dots. The QDs-first ligand-QDs structure can act as a charge transfer center, and its longitudinal conductivity is better than that of flake crystals, thereby improving the electrical conductivity of the quantum dot film. Since the straight-chain organic carboxylic acid containing the first active group has a strong affinity with the transport layer, when the quantum dot film is used as the light-emitting layer of the quantum dot light-emitting diode, the contact surface between the quantum dot film and the transport layer is the straight-chain organic carboxylic acid containing the first active group, and the QDs / ETL interface is mainly composed of the straight-chain organic carboxylic acid containing the first active group. The quantum dots on the interface can be connected to the electron transport material such as ZnO through the straight-chain organic carboxylic acid containing the first active group to form an electron transport material-first ligand-QDs structure, which modifies the QDs / ETL interface, reduces the contact angle of spin coating, improves the film quality of the electron transport material, enhances the transmission capacity of interface electrons, makes it easier for electrons to be injected from the electron transport material into the quantum dots, and improves the luminous efficiency and service life of the quantum dot light-emitting device.
[0097] In some embodiments, the third reactive group is selected from one of hydroxyl, carboxyl, thiol, amino, and nitro, preferably hydroxyl, and the polarity of the third reactive group is stronger than that of the first reactive group.
[0098] In some embodiments, the third ligand is selected from at least one of hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate.
[0099] In some embodiments, the first ligand is suberic acid, and the third ligand is HEMA, that is, the surface of the quantum dots in the quantum dot film is simultaneously bound to suberic acid and HEMA ligands. Figure 5As shown in the figure, HEMA is used as the third ligand, and the third ligands on the surfaces of different quantum dots are connected through the polymerization reaction between the ligands, thereby connecting the quantum dots in the same layer, shortening the distance between the quantum dots in the same layer. On the other hand, it can be seen from the double bond bonding path shown in the figure that the quantum dots in different layers are also connected, thereby shortening the distance between the quantum dots between the layers and polymerizing to form a chain polymer. The quantum dots are arranged in an orderly manner as shown in the figure, and are closely connected by the ligands to form a preferred orientation, providing a basic skeleton for the crystallization of the quantum dot layer. Due to the shortened distance between the quantum dots, the charge transport of the interlayer quantum dots and the charge transport of the quantum dots within the layer are enhanced. The chain polymer forms a lamellar crystal through the folding and rotation of the molecules during the heat treatment process such as 100°C after the metal oxide material such as ZnO of the electron transport layer is spin-coated. At the same time, the quantum dot layers can also be connected by suberic acid to form a QDs-first ligand-QDs structure, and the formed flake crystals are connected and stacked to form layered crystals. This layered crystal structure has a strong carrier transmission capacity between quantum dots. The QDs-first ligand-QDs structure can act as a charge transmission center, and the longitudinal conductivity is better than that of flake crystals, which improves the conductivity of the quantum dot film. Since suberic acid has a strong affinity with the transport layer, the contact surface between the quantum dot film and the transport layer is a suberic acid ligand, and the QDs / ETL interface is mainly suberic acid. The quantum dots on the interface can be connected to ZnO through suberic acid to form an electron transport material-first ligand-QDs structure, which modifies the QDs / ETL interface, reduces the contact angle of spin coating, improves the film quality of zinc oxide, and enhances the transmission capacity of interface electrons, making it easier for electrons to be injected from the electron transport layer into the quantum dots, thereby improving the luminous efficiency and service life of quantum dot light-emitting diode devices.
[0100] In the fourth embodiment based on the above embodiment, the quantum dot surface is simultaneously combined with the first ligand and the fourth ligand, wherein the fourth ligand is a MOF monomer, and the MOF monomer contains at least three fourth active groups that can be combined with quantum dots, and the polarity of the fourth active group is stronger than the polarity of the first active group. MOF monomer is an organic monomer material for forming MOF (metal-organic framework material). MOF monomer is combined with the surface of quantum dots. On the one hand, MOF monomer has self-assembly characteristics. Therefore, in the process of quantum dot film formation, driven by MOF monomer, the surface is combined with MOF quantum dots in an orderly manner, which improves the film forming processability and uniform order of quantum dots. On the other hand, a quantum dot surface is combined with multiple MOF monomers at the same time to form a skeleton structure similar to MOF, which can reduce the surface defects of quantum dots. At the same time, the micropores between MOF monomers in the skeleton structure similar to MOF are filled by quantum dots, thereby improving the crystallinity of quantum dot film and obtaining a high-quality superlattice quantum dot structure. Two aspects act simultaneously, and finally form an ordered high-quality superlattice structure (similar to the skeleton structure of MOF). In this case, the ordered high-quality superlattice structure can solve the problem of many defects in quantum dot films and loose and disordered structures, effectively improve the transmission capacity of carriers, improve the conductivity of quantum dot films, and then when the quantum dot material is used as the light-emitting layer material of quantum dot light-emitting diodes, it can enhance the ability of excitons to recombine in the light-emitting layer, reduce the charge accumulation at the interface between the quantum dot light-emitting layer and the electron transport layer, solve the problem of device charge imbalance caused by the hole mobility being much lower than the electron mobility, and finally improve the service life and luminous efficiency of quantum dot light-emitting devices. Furthermore, since the first ligand contains more than three first active groups at the same time, a MOF monomer can simultaneously connect multiple quantum fixed particles, thereby shortening the distance between quantum dots, reducing the electron transmission distance between quantum dots, and further improving the carrier migration ability of quantum dots. In addition, the quantum dot film provided by the embodiment of the present application has a large steric hindrance of the MOF monomer on the surface of the quantum dot, which can prevent agglomeration between quantum dots, thereby improving its film processing performance. On this basis, straight-chain organic carboxylic acid ligands are used to fill the gaps in MOF monomers to form a QDs-first ligand-QDs structure, and QDs-first ligand-QDs are used to extend outward in a chain to fill the gaps in the three-dimensional skeleton and surround the three-dimensional longitudinal skeleton to form a transverse structure. The grain size formed in this way is large, and it is a large grain structure with ultra-long-range carrier conduction capability, which increases the maximum diffusion length of carriers, improves the carrier transmission capacity of the quantum dot film, reduces the number of grain boundaries and the corresponding number of defects, and improves the luminescence efficiency and service life of the device.
[0101] In some embodiments, the fourth active group is selected from a hydroxyl group, a carboxyl group, a thiol group, and an amino group. The fourth active groups in the same MOF monomer may be the same or different.
[0102] In some embodiments, the fourth ligand is selected from the compound shown in the following formula 4, wherein X 4 , X 5 , X 6 is the same or different fourth active group:
[0103]
[0104] The compound shown in Formula 4 contains three fourth active groups that can bind to quantum dots. The three fourth active groups can bind to three quantum dots, thereby weaving the quantum dot particles into a network structure to form a stable and orderly superlattice structure. The ligand structure on the surface of the quantum dot has a high degree of conjugation. Therefore, using the compound shown in Formula 4 as the surface ligand of the quantum dot can further improve the carrier transport performance of the quantum dot by means of the conjugation effect.
[0105] In some embodiments, the first ligand is suberic acid, and the fourth ligand is 1,3,5-tri(4-carboxyphenyl)benzene. That is, the surface of the quantum dots in the quantum dot film is simultaneously bound to suberic acid and 1,3,5-tri(4-carboxyphenyl)benzene. Figure 6 As shown, 1,3,5-tri(4-carboxyphenyl)benzene and suberic acid are used as ligands, and the three-coordination site self-assembly property of 1,3,5-tri(4-carboxyphenyl)benzene forms a large MOF-like superlattice skeleton. As shown in the figure, a single MOF is coordinated with three quantum dots, and a quantum dot has multiple ligands covering all the dangling bonds on the surface of the quantum dot. All quantum dots are connected by the connecting effect of MOF monomers to form a large three-dimensional structure. Such a three-dimensional structure has good longitudinal conductivity because the longitudinal direction is composed of a MOF-like skeleton. However, such a three-dimensional structure has many gaps and micropores. When using suberic acid ligands, the gaps formed are filled by suberic acid to form a QDs-first ligand-QDs structure, and QDs-first ligand-QDs are used to extend outward in a chain to fill the gaps in the three-dimensional skeleton and surround the three-dimensional longitudinal skeleton to form a transverse structure. The grain size formed in this way is large, and it is a large grain structure with ultra-long-range carrier conduction capability, which increases the maximum diffusion length of carriers, improves the carrier transmission capacity of the quantum dot film, reduces the number of grain boundaries and the corresponding number of defects, and improves the luminescence efficiency and life of the device.
[0106] Combination Figure 7 A third aspect of an embodiment of the present invention provides a quantum dot light-emitting diode, comprising an anode and a cathode arranged relatively to each other, a quantum dot light-emitting layer arranged between the cathode and the anode, and an electron transport layer arranged between the quantum dot light-emitting layer and the cathode, wherein the quantum dot light-emitting layer is a method for preparing a quantum dot film obtained by the above-mentioned preparation method; or the quantum dot light-emitting layer is the above-mentioned quantum dot film.
[0107] The quantum dot light-emitting diode provided by the embodiment of the present invention uses the above-mentioned quantum dot film as the light-emitting layer, and the first ligand on the quantum dots on the surface of the quantum dot film combines with the metal oxide in the electron transport layer to form a QDs / ETL interface containing metal ions, so that the binding force between the quantum dots and the electron transport layer is enhanced, the contact angle is reduced, and a mixed phase interface or an interface with very small intrinsic interface tension is formed, which is beneficial to the injection of electrons from the electron transport layer into the quantum dots, reduces the charge accumulation at the QD / ZnO interface and the device damage and attenuation caused by stress, so that the service life and luminous efficiency of the device are improved. Therefore, the luminous efficiency and service life of the device can be effectively improved.
[0108] In some embodiments, the quantum dot light emitting diode further comprises a hole functional layer disposed between the anode and the quantum dot light emitting layer. The hole functional layer comprises at least one of a hole injection layer and a hole transport layer.
[0109] In some embodiments, the quantum dot light emitting diode further includes an electron injection layer disposed between the cathode and the electron transport layer.
[0110] A fourth aspect of an embodiment of the present invention provides a method for preparing a quantum dot light-emitting diode, which at least includes preparing a quantum dot light-emitting layer, and the quantum dot light-emitting layer is prepared by the above-mentioned preparation method.
[0111] In the method for preparing a quantum dot light-emitting diode provided by an embodiment of the present invention, when a quantum dot film contacts a metal compound in an electron transport layer, a straight-chain organic carboxylic acid after hydrolysis of compound A combines with metal ions to obtain a quantum dot surface of quantum dot-first ligand-metal ion, thereby forming a QDs / ETL interface containing metal ions with the metal oxide in the electron transport layer, especially zinc oxide, so that the binding force between the quantum dots and the electron transport layer is enhanced, the contact angle is reduced, and a mixed phase interface or an interface with very small intrinsic tension is formed, which is conducive to the injection of electrons from the electron transport layer into the quantum dots, reduces the charge accumulation at the QD / ZnO interface and the device damage and attenuation caused by stress, so that the device service life and luminous efficiency are improved, which is of great significance for realizing a high-quality and strong-binding multilayer film structure.
[0112] The following describes the invention in conjunction with specific embodiments.
[0113] Example 1
[0114] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0115] At room temperature and in an inert gas atmosphere, a mixture of monomethyl suberate and n-octanoic acid is added to a non-polar solvent of CdZnSe / ZnSe quantum dots. Then, after the temperature is raised to 100-200°C, a ligand exchange is performed for 20-40 minutes to obtain a quantum dot solution with monomethyl suberate as a ligand. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged multiple times in n-hexane and ethanol, and finally the obtained quantum dot product is dispersed in n-octane.
[0116] After the HTL layer is deposited on the anode substrate, a quantum dot solution with monomethyl suberate as a ligand is deposited to prepare a quantum dot prefabricated film; a layer of ethanol solution (containing 1% water) containing 1% by weight of KOH and 1% by weight of zinc acetate is deposited on the quantum dot prefabricated film as a quantum dot surface modifier and hydrolysis reaction catalyst, and heated at 70°C for 60 minutes.
[0117] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0118] Example 2
[0119] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0120] At room temperature and in an inert gas atmosphere, a mixture of monomethyl pimelate and n-octanoic acid is added to a non-polar solvent of CdZnSe / ZnSe / ZnS quantum dots. Then, after heating to 100-200°C, ligand exchange is performed for 20-40 minutes to obtain a quantum dot solution with monomethyl pimelate as a ligand. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged in n-hexane and ethanol for multiple times, and finally the obtained quantum dot product is dispersed in n-octane.
[0121] After the HTL layer is deposited on the anode substrate, a quantum dot solution with monomethyl pimelate as a ligand is deposited to prepare a quantum dot prefabricated film; a layer of ethanol solution (containing 1% water) containing 1% by weight of KOH and 1% by weight of zinc acetate is deposited on the quantum dot prefabricated film as a quantum dot surface modifier and hydrolysis reaction catalyst, and heated at 70°C for 60 minutes.
[0122] The ETL layer, i.e., the ZnO layer, was deposited and heated at 100°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0123] Example 3
[0124] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0125] At room temperature and in an inert gas atmosphere, a mixture of monomethyl azelaic acid and octanoic acid is added to a non-polar solvent of CdZnSe / ZnSe / ZnS quantum dots. Then, after heating to 100-200°C, ligand exchange is performed for 20-40 minutes to obtain a quantum dot solution with monomethyl azelaic acid as a ligand. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged in n-hexane and ethanol for multiple times, and finally the obtained quantum dot product is dispersed in n-octane.
[0126] After the HTL layer is deposited on the anode substrate, a quantum dot solution with monomethyl azelaic acid as a ligand is deposited to prepare a quantum dot prefilm; a layer of ethanol solution (containing 1% water) containing 1% by weight of KOH and 1% by weight of zinc acetate is deposited on the quantum dot prefilm as a quantum dot surface modifier and hydrolysis reaction catalyst, and heated at 70°C for 60 minutes.
[0127] The ETL layer, i.e., the ZnO layer, was deposited and heated at 60°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0128] Example 4
[0129] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0130] At room temperature and in an inert gas atmosphere, a mixture of monomethyl adipate and n-octanoic acid is added to a non-polar solvent of CdZnSeS / ZnSe quantum dots. Then, after heating to 100-200°C, ligand exchange is performed for 20-40 minutes to obtain a quantum dot solution with monomethyl adipate as a ligand. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged in n-hexane and ethanol for multiple times, and finally the obtained quantum dot product is dispersed in n-octane.
[0131] After the HTL layer is deposited on the anode substrate, a quantum dot solution with monomethyl adipate as a ligand is deposited to prepare a quantum dot prefabricated film; a layer of ethanol solution (containing 1% water) containing 1% by weight of KOH and 1% by weight of zinc acetate is deposited on the quantum dot prefabricated film as a quantum dot surface modifier and hydrolysis reaction catalyst, and heated at 70°C for 60 minutes.
[0132] The ETL layer, i.e., the ZnO layer, was deposited, heated at 120°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0133] Comparative Example 1
[0134] A method for preparing a quantum dot light-emitting tube comprises the following steps:
[0135] After the HTL layer was deposited on the anode substrate, CdZnSe / ZnSe quantum dots with oleic acid as ligand were deposited and heated at 70°C for 60 min to prepare the quantum dot light-emitting layer;
[0136] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0137] Comparative Example 2
[0138] A method for preparing a quantum dot light-emitting diode comprises the following steps:
[0139] After the HTL layer was deposited on the anode substrate, CdZnSe / ZnSe / ZnS quantum dots with oleic acid as ligand were deposited and heated at 70°C for 60 min to prepare the quantum dot light-emitting layer;
[0140] The ETL layer, i.e., the ZnO layer, was deposited and heated at 100°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0141] Comparative Example 3
[0142] A method for preparing a quantum dot light-emitting tube comprises the following steps:
[0143] After the HTL layer was deposited on the anode substrate, CdZnSeS / ZnSe / ZnS quantum dots with oleic acid as ligand were deposited and heated at 70°C for 60 min to prepare the quantum dot light-emitting layer;
[0144] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0145] Comparative Example 4
[0146] A method for preparing a quantum dot light-emitting diode comprises the following steps:
[0147] After the HTL layer was deposited on the anode substrate, CdZnSeS / ZnS quantum dots with oleic acid as ligand were deposited and heated at 70°C for 60 min to prepare the quantum dot light-emitting layer;
[0148] The ETL layer, i.e., the ZnO layer, was deposited and heated at 100°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0149] The quantum dot light-emitting diodes of Examples 1-4 and Comparative Examples 1-4 were subjected to life tests. The test method is as follows: the device is driven by a constant current or voltage, and the time required for the brightness to decrease to a certain proportion of the maximum brightness. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and the life is the measured life. In order to shorten the test cycle, the device life test is usually carried out by accelerating device aging at high brightness with reference to the OLED device test, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula, for example: the life under 1000nit is calculated as T951000nit. The specific calculation formula is as follows:
[0150]
[0151] Where, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, for OLED, the value is usually 1.6~2. In this experiment, the lifespan of several groups of green QLED devices at rated brightness was measured and the A value was 1.7.
[0152] The life test system was used to test the life of the corresponding devices. The test conditions were: at room temperature and the air humidity was 30-60%. The test results are shown in Table 1 below:
[0153] Table 1
[0154] Comparative Example 1 Example 1 Comparative Example 2 Example 2 Comparative Example 3 Example 3 Comparative Example 4 Example 4 T95(h) 1.15 1.78 0.89 1.59 0.61 1.19 0.48 0.96
[0155] Example 5
[0156] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0157] At room temperature and in an inert gas atmosphere, a mixture of methyl suberate and octanoic acid was added to the non-polar solvent of CdZnSe / ZnSe quantum dots, and after heating to 100°C, ligand exchange was performed for 4 hours to obtain a first quantum dot solution with methyl suberate as a ligand. At room temperature and in an inert gas atmosphere, a mixture of 9-nitroanthracene and fatty acids was added to a certain amount of the first quantum dot solution, and the molar ratio of 9-nitroanthracene to quantum dots was 1:2. Then, after heating to 100°C, ligand exchange was performed for 16 hours to obtain a second quantum dot solution with 9-nitroanthracene and methyl suberate as ligands. After the reaction was completed, the product was repeatedly dissolved, precipitated and centrifuged multiple times by n-hexane and ethanol, and finally the obtained quantum dot product was dispersed in n-octane.
[0158] After the HTL layer is deposited on the anode substrate, a second quantum dot solution is deposited, and then a layer of 1% by mass NaOH ethanol solution is deposited as a quantum dot reaction catalyst, and the mixture is heated at 70° C. for 30 minutes to prepare a quantum dot light-emitting layer;
[0159] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0160] Example 6
[0161] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0162] At room temperature and in an inert gas atmosphere, a mixture of methyl suberate and octanoic acid was added to a non-polar solvent of CdZnSe / ZnSe / ZnS quantum dots, and after heating to 100°C, a ligand exchange was performed for 4 hours to obtain a first quantum dot solution with methyl suberate as a ligand. At room temperature and in an inert gas atmosphere, a mixture of 1-nitronaphthalene and fatty acids was added to a certain amount of the first quantum dot solution, and the molar ratio of 1-nitronaphthalene to quantum dots was 1:2. Then, after heating to 100°C, a ligand exchange was performed for 16 hours to obtain a second quantum dot solution with 1-nitronaphthalene and methyl suberate as ligands. After the reaction was completed, the product was repeatedly dissolved, precipitated and centrifuged multiple times by n-hexane and ethanol, and finally the obtained quantum dot product was dispersed in n-octane.
[0163] After the HTL layer is deposited on the anode substrate, a second quantum dot solution is deposited, and then a layer of KOH ethanol solution containing 5% by mass as a quantum dot reaction catalyst is deposited, and heated at 70° C. for 30 minutes to prepare a quantum dot light-emitting layer;
[0164] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0165] Example 7
[0166] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0167] At room temperature and in an inert gas atmosphere, a mixture of monomethyl pimelate and n-octanoic acid was added to the non-polar solvent of CdZnSeS / ZnSe / ZnS quantum dots, and after heating to 100°C, ligand exchange was performed for 4 hours to obtain a first quantum dot solution with monomethyl pimelate as a ligand. At room temperature and in an inert gas atmosphere, a mixture of 9-nitroanthracene and fatty acids was added to a certain amount of the first quantum dot solution, and the molar ratio of 9-nitroanthracene to quantum dots was 1:2. Then, after heating to 100°C, ligand exchange was performed for 16 hours to obtain a second quantum dot solution with 9-nitroanthracene and monomethyl pimelate as ligands. After the reaction was completed, the product was repeatedly dissolved, precipitated and centrifuged multiple times by n-hexane and ethanol, and finally the obtained quantum dot product was dispersed in n-octane.
[0168] After the HTL layer is deposited on the anode substrate, a second quantum dot solution is deposited, and then a layer of 10% by weight octanoic acid ethanol solution is deposited as a quantum dot reaction catalyst, and the mixture is heated at 70° C. for 30 minutes to prepare a quantum dot light-emitting layer;
[0169] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0170] Example 8
[0171] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0172] At room temperature and in an inert gas atmosphere, a mixture of monomethyl azelaic acid and octanoic acid was added to the non-polar solvent of CdZnSeS / ZnSe quantum dots, and after heating to 100°C, the ligand was exchanged for 4 hours to obtain a first quantum dot solution with monomethyl azelaic acid as a ligand. At room temperature and in an inert gas atmosphere, a mixture of 1-nitroanthracene and fatty acids was added to a certain amount of the first quantum dot solution, and the molar ratio of 1-nitroanthracene to quantum dots was 1:2. Then, after heating to 100°C, the ligand was exchanged for 16 hours to obtain a second quantum dot solution with 1-nitroanthracene and monomethyl azelaic acid as ligands. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged multiple times by n-hexane and ethanol, and finally the obtained quantum dot product is dispersed in n-octane.
[0173] After the HTL layer is deposited on the anode substrate, a second quantum dot solution is deposited, and then a layer of 5% by weight octanoic acid ethanol solution is deposited as a quantum dot reaction catalyst, and the mixture is heated at 70° C. for 30 minutes to prepare a quantum dot light-emitting layer;
[0174] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0175] The quantum dot light-emitting diodes of Examples 5-8 were subjected to life tests. The test method is: the time required for the device to reduce its brightness to a certain proportion of the maximum brightness under constant current or voltage drive, and the time for the brightness to drop to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually carried out by accelerating device aging at high brightness with reference to the OLED device test, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula, for example: the life under 1000nit is calculated as T951000nit. The specific calculation formula is as follows:
[0176]
[0177] Where, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, for OLED, the value is usually 1.6~2. In this experiment, the lifespan of several groups of green QLED devices at rated brightness was measured and the A value was 1.7.
[0178] The life test system was used to test the life of the corresponding devices. The test conditions were: at room temperature and the air humidity was 30-60%. The test results are shown in Table 2 below:
[0179] Table 2
[0180] Example 5 Example 6 Example 7 Example 8 T95(h) 1.91 1.48 1.27 1.12
[0181] Example 9
[0182] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0183] At room temperature and in an inert gas atmosphere, a mixture of monomethyl suberate and n-octanoic acid was added to the non-polar solvent of CdZnSe / ZnSe quantum dots to form a mixed solution system. After heating to 100°C, ligand exchange was performed for 2h to obtain a quantum dot solution with monomethyl suberate as a ligand. A small amount of a mixture of n-octanoic acid and ethanol was then added, and the first quantum dot solution with suberic acid as the main ligand was obtained after hydrolysis at 80°C for 2h. A mixture of HEMA and n-octanoic acid was added to a certain amount of the first quantum dot solution. Then, after heating to 60°C, ligand exchange was performed for 16h, and the molar ratio of HEMA added to the quantum dots was 50:1, to obtain a second quantum dot solution with suberic acid and HEMA as ligands. After the reaction was completed, the product was repeatedly dissolved, precipitated and centrifuged by n-hexane and ethanol for multiple times, and finally the obtained quantum dot product was dispersed in n-octane. An ethanol solution containing 5% AIBN and 2% EGDMA was added to the second quantum dot as a reaction catalyst for the polymerization of quantum dot ligands.
[0184] After the HTL layer is deposited on the anode substrate, a second quantum dot solution is deposited and heated at 70°C for 30 min to obtain a polymerized polar quantum dot film;
[0185] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0186] Example 10
[0187] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0188] At room temperature and in an inert gas atmosphere, a mixture of monomethyl pimelate and n-octanoic acid was added to a non-polar solvent of CdZnSe / ZnSe / ZnS quantum dots to form a mixed solution system. After heating to 100°C, ligand exchange was performed for 2 hours to obtain a quantum dot solution with monomethyl pimelate as a ligand. A small amount of a mixture of n-octanoic acid and ethanol was then added, and the first quantum dot solution with pimelic acid as the main ligand was obtained after hydrolysis at 80°C for 2 hours. A mixture of HEMA and n-octanoic acid was added to a certain amount of the first quantum dot solution. Then, after heating to 60°C, ligand exchange was performed for 16 hours, and the molar ratio of the amount of HEMA added to the quantum dots was 50:1, and a second quantum dot solution with pimelic acid and HEMA as ligands was obtained. After the reaction was completed, the product was repeatedly dissolved, precipitated and centrifuged by n-hexane and ethanol for many times, and finally the obtained quantum dot product was dispersed in n-octane. An ethanol solution containing 5% AIBN and 2% EGDMA was added to the second quantum dot as a reaction catalyst for the polymerization of quantum dot ligands.
[0189] After the HTL layer is deposited on the anode substrate, the second quantum dot solution is deposited and heated at 70° C. for 30 min to obtain a polymerized polar quantum dot film.
[0190] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0191] Embodiment 11
[0192] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0193] At room temperature and in an inert gas atmosphere, a mixture of monomethyl azelaic acid and octanoic acid was added to the non-polar solvent of CdZnSeS / ZnSe / ZnS quantum dots to form a mixed solution system. After heating to 100°C, ligand exchange was performed for 2 hours to obtain a quantum dot solution with monomethyl azelaic acid as a ligand. A small amount of a mixture of octanoic acid and ethanol was then added, and the first quantum dot solution with azelaic acid as the main ligand was obtained after hydrolysis at 80°C for 2 hours. A mixture of HEMA and octanoic acid was added to a certain amount of the first quantum dot solution. Then, after heating to 60°C, ligand exchange was performed for 16 hours, and the molar ratio of HEMA added to the quantum dots was 50:1, and a second quantum dot solution with azelaic acid and HEMA as ligands was obtained. After the reaction was completed, the product was repeatedly dissolved, precipitated and centrifuged by n-hexane and ethanol for many times, and finally the obtained quantum dot product was dispersed in n-octane. An ethanol solution containing 5% AIBN and 2% EGDMA was added to the second quantum dot as a reaction catalyst for the polymerization of quantum dot ligands.
[0194] After the HTL layer is deposited on the anode substrate, a second quantum dot solution is deposited and heated at 70°C for 30 min to obtain a polymerized polar quantum dot film;
[0195] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0196] Example 12
[0197] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0198] At room temperature and in an inert gas atmosphere, a mixture of monomethyl sebacic acid and octanoic acid was added to a non-polar solvent of CdZnSeS / ZnS quantum dots to form a mixed solution system. After heating to 100°C, ligand exchange was performed for 2 hours to obtain a quantum dot solution with monomethyl sebacic acid as a ligand. A small amount of a mixture of octanoic acid and ethanol was then added, and the first quantum dot solution with sebacic acid as the main ligand was obtained after hydrolysis at 80°C for 2 hours. A mixture of HEMA and octanoic acid was added to a certain amount of the first quantum dot solution. Then, after heating to 60°C, ligand exchange was performed for 16 hours, and the molar ratio of the amount of HEMA added to the quantum dots was 50:1, and a third quantum dot solution with sebacic acid and HEMA as ligands was obtained. After the reaction was completed, the product was repeatedly dissolved, precipitated and centrifuged by n-hexane and ethanol for many times, and finally the obtained quantum dot product was dispersed in n-octane. An ethanol solution containing 5% AIBN and 2% EGDMA was added to the second quantum dot as a reaction catalyst for the polymerization of quantum dot ligands.
[0199] After the HTL layer is deposited on the anode substrate, a second quantum dot solution is deposited and heated at 70°C for 30 min to obtain a polymerized polar quantum dot film;
[0200] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0201] The quantum dot light-emitting diodes of Examples 9-12 were subjected to life tests. The test method is: the device is driven by a constant current or voltage, and the time required for the brightness to decrease to a certain proportion of the maximum brightness. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually carried out by accelerating device aging at high brightness with reference to the OLED device test, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula, for example: the life under 1000nit is calculated as T951000nit. The specific calculation formula is as follows:
[0202]
[0203] Where, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, for OLED, the value is usually 1.6~2. In this experiment, the lifespan of several groups of green QLED devices at rated brightness was measured and the A value was 1.7.
[0204] The life test system was used to test the life of the corresponding devices. The test conditions were: at room temperature and the air humidity was 30-60%. The test results are shown in Table 3 below:
[0205] Table 3
[0206] Example 9 Example 10 Embodiment 11 Example 12 T95(h) 2.15 1.50 1.35 1.25
[0207] Embodiment 13
[0208] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0209] At room temperature and in an inert gas atmosphere, a mixture of monomethyl suberate and n-octanoic acid was added to the non-polar solvent of CdZnSeS / ZnS quantum dots. Then, after heating to 100°C, ligand exchange was performed for 1h to obtain a first quantum dot solution with suberic acid as a ligand. Then, a small amount of a mixture of fatty acids and ethanol was added, and the second quantum dot solution with suberic acid as a ligand was obtained after hydrolysis at 100°C for 4h. At room temperature and in an inert gas atmosphere, a fatty acid mixture of 1,3,5-tri(4-carboxyphenyl)benzene was added to the second quantum dot solution. Then, after heating to 100°C, ligand exchange was performed for 16h to obtain a third quantum dot solution with 1,3,5-tri(4-carboxyphenyl)benzene and suberic acid as ligands, and the molar ratio of 1,3,5-tri(4-carboxyphenyl)benzene to quantum dots was 1:1. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged through n-hexane and ethanol for multiple times, and finally the obtained quantum dot product is dispersed in n-octane.
[0210] After the HTL layer is deposited on the anode substrate, a third quantum dot solution is deposited and heated at 70° C. for 30 min to obtain a polymerized polar quantum dot film;
[0211] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0212] Embodiment 14
[0213] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0214] At room temperature and in an inert gas atmosphere, a mixture of monomethyl pimelate and n-octanoic acid in a non-polar solvent of CdZnSe / ZnSe / ZnS quantum dots was added. Then, after heating to 100°C, the ligand was exchanged for 1h to obtain a first quantum dot solution with pimelic acid as a ligand. Then, a small amount of a mixture of fatty acids and ethanol was added, and the second quantum dot solution with pimelic acid as a ligand was obtained after hydrolysis at 100°C for 4h. At room temperature and in an inert gas atmosphere, a fatty acid mixture of 1,3,5-tri(4-carboxyphenyl)benzene was added to the second quantum dot solution. Then, after heating to 100°C, a ligand exchange was performed for 16h to obtain a third quantum dot solution with 1,3,5-tri(4-carboxyphenyl)benzene and pimelic acid as ligands, and the molar ratio of 1,3,5-tri(4-carboxyphenyl)benzene to quantum dots was 1:1. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged through n-hexane and ethanol for multiple times, and finally the obtained quantum dot product is dispersed in n-octane.
[0215] After the HTL layer is deposited on the anode substrate, a third quantum dot solution is deposited and heated at 70° C. for 30 min to obtain a polymerized polar quantum dot film;
[0216] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0217] Embodiment 15
[0218] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0219] At room temperature and in an inert gas atmosphere, a mixture of monomethyl azelaic acid and octanoic acid was added to a non-polar solvent of CdZnSeS / ZnSe / ZnS quantum dots. Then, after heating to 100°C, the ligand was exchanged for 1h to obtain a first quantum dot solution with azelaic acid as a ligand. Then, a small amount of a mixture of fatty acids and ethanol was added, and the second quantum dot solution with azelaic acid as a ligand was obtained after hydrolysis at 100°C for 4h. At room temperature and in an inert gas atmosphere, a fatty acid mixture of 1,3,5-tri(4-carboxyphenyl)benzene was added to the second quantum dot solution. Then, after heating to 100°C, a ligand exchange was performed for 16h to obtain a third quantum dot solution with 1,3,5-tri(4-carboxyphenyl)benzene and azelaic acid as ligands, and the molar ratio of 1,3,5-tri(4-carboxyphenyl)benzene to quantum dots was 1:1. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged through n-hexane and ethanol for multiple times, and finally the obtained quantum dot product is dispersed in n-octane.
[0220] After the HTL layer is deposited on the anode substrate, a third quantum dot solution is deposited and heated at 70° C. for 30 min to obtain a polymerized polar quantum dot film;
[0221] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0222] Example 16
[0223] A quantum dot light emitting diode, the preparation method of which comprises the following steps:
[0224] At room temperature and in an inert gas atmosphere, a mixture of monomethyl sebacic acid and octanoic acid was added to a non-polar solvent of CdZnSeS / ZnSe quantum dots. Then, after heating to 100°C, the ligand exchange was carried out for 1h to obtain a first quantum dot solution with sebacic acid as a ligand. Then, a small amount of a mixture of fatty acids and ethanol was added, and the second quantum dot solution with sebacic acid as a ligand was obtained after hydrolysis at 100°C for 4h. At room temperature and in an inert gas atmosphere, a fatty acid mixture of 1,3,5-tri(4-carboxyphenyl)benzene was added to the second quantum dot solution. Then, after heating to 100°C, the ligand exchange was carried out for 16h to obtain a third quantum dot solution with 1,3,5-tri(4-carboxyphenyl)benzene and sebacic acid as ligands, and the molar ratio of 1,3,5-tri(4-carboxyphenyl)benzene to quantum dots was 1:1. After the reaction is completed, the product is repeatedly dissolved, precipitated and centrifuged through n-hexane and ethanol for multiple times, and finally the obtained quantum dot product is dispersed in n-octane.
[0225] After the HTL layer is deposited on the anode substrate, a third quantum dot solution is deposited and heated at 70° C. for 30 min to obtain a polymerized polar quantum dot film;
[0226] The ETL layer, i.e., the ZnO layer, was deposited and heated at 80°C for 30 min, and then the Al electrode was evaporated and packaged with electronic glue to obtain the QLED device.
[0227] The quantum dot light-emitting diodes of Examples 13-16 were subjected to life tests. The test method is: the time required for the brightness of the device to decrease to a certain proportion of the maximum brightness under constant current or voltage drive, the time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually carried out by accelerating device aging at high brightness with reference to the OLED device test, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula, for example: the life under 1000nit is calculated as T951000nit. The specific calculation formula is as follows:
[0228]
[0229] Where, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, LL is 1000nit, A is the acceleration factor, for OLED, the value is usually 1.6~2. In this experiment, the lifespan of several groups of green QLED devices at rated brightness was measured and the A value was 1.7.
[0230] The life test system is used to test the life of the corresponding devices. The test conditions are: at room temperature and the air humidity is 30-60%. The test results are shown in Table 4 below:
[0231] Table 4
[0232] Embodiment 13 Embodiment 14 Embodiment 15 Example 16 T95(h) 2.15 1.50 1.35 1.25
[0233] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a quantum dot film, characterized in that: The following steps are involved: Under an inert atmosphere, a fatty acid solution of compound A and a mixed solution system of first quantum dots are provided, and a ligand exchange reaction is performed under a first heating condition to prepare second quantum dots with compound A bound to the surface; wherein the general structural formula of compound A is as follows: 1 is a first active group combined with the first quantum dot, wherein the first active group is selected from a carboxyl group; R 1 -(CH2) n -, R 2 For straight chain C m H 2m+1 , m and n are positive integers, and the value range of n+m is 2 to 12; after performing the ligand exchange reaction under the first heating condition, the method further comprises: adding a fourth ligand to the reaction system of the second quantum dot having the compound A bound to the surface under an inert atmosphere, and performing the ligand exchange reaction under the fourth heating condition to prepare the second quantum dot having the compound A and the fourth ligand bound to the surface at the same time; the fourth ligand is selected from the compound shown in the following formula 4, wherein X 4 , X 5 , X 6 are the same or different fourth active groups, wherein the fourth active group is selected from one of hydroxyl, carboxyl, thiol and amino; Providing a substrate, and depositing second quantum dots having compound A and a fourth ligand simultaneously bound to the surface of the substrate on the substrate to prepare a quantum dot prefabricated film; The second quantum dot having compound A and the fourth ligand bound to the surface is mixed with a mixed solution containing an ester hydrolysis catalyst, and heated to cause compound A on the surface of the second quantum dot having compound A and the fourth ligand bound to the surface to undergo an ester hydrolysis reaction to generate a compound having a general structural formula of X 1 -CH2-R 1 -COOH as the first ligand, obtaining a second quantum dot with the first ligand bound to the surface, and performing film forming treatment on the substrate to prepare a quantum dot film.
2. The method for preparing a quantum dot thin film according to claim 1, wherein: The compound A is at least one selected from monomethyl suberate, monoethyl pimelate, and monoethyl azelaic acid.
3. The method for preparing a quantum dot thin film according to claim 1, wherein: In the mixed solution system of the fatty acid solution of compound A and the first quantum dots, the molar ratio of compound A to the first quantum dots is 50-100:1; and / or The fatty acid in the fatty acid solution of compound A is selected from at least one of n-octanoic acid, acetic acid, n-hexanoic acid, n-butyric acid, and n-valeric acid; and / or The step of providing a mixed solution system of a fatty acid solution of compound A and a first quantum dot comprises: separately preparing a fatty acid solution of compound A and a non-polar solution of the first quantum dot, mixing them, and obtaining the mixed solution system.
4. The method for preparing a quantum dot thin film according to any one of claims 1 to 3, characterized in that: In the step of performing a ligand exchange reaction under a first heating condition, the temperature of the first heating condition is 100° C. to 200° C., and the time of the ligand exchange reaction is 20 min to 40 min; and / or The substrate is a substrate having an electron transport material on its surface.
5. The method for preparing a quantum dot film according to claim 4, characterized in that: The electron transport material is metal compound nanoparticles.
6. The method for preparing a quantum dot thin film according to claim 5, characterized in that: The electron transport material is zinc oxide nanoparticles.
7. The method for preparing a quantum dot thin film according to any one of claims 1 to 3, characterized in that: In the step of performing a ligand exchange reaction under the fourth heating condition, the temperature of the fourth heating condition is 100°C~200°C, and the time of the exchange reaction is 8h~16h; and in the step of performing a ligand exchange reaction under the first heating condition, the temperature of the first heating condition is 100°C~150°C, and the time of the exchange reaction is 1h~2h.
8. A quantum dot film, characterized in that: The quantum dot film is composed of quantum dots, and the quantum dots include a quantum dot matrix, a first ligand bound to the surface of the quantum dot matrix, and a fourth ligand bound to the surface of the quantum dot matrix, wherein the first ligand is X 1 -CH2-R 1 -COOH, X 1 is the first active group combined with the quantum dot matrix; R 1 -(CH2) n -, n is a positive integer, and the value of n satisfies the range of 1 to 10; the first active group is selected from a carboxyl group; the fourth ligand is selected from a compound shown in the following formula 4, wherein X 4 , X 5 , X 6 are the same or different fourth reactive groups, wherein the fourth reactive group is selected from one of hydroxyl, carboxyl, thiol and amino groups: 。 9. A quantum dot light emitting diode, characterized in that: The invention comprises an anode and a cathode arranged opposite to each other, a quantum dot light-emitting layer arranged between the cathode and the anode, and an electron transport layer arranged between the quantum dot light-emitting layer and the cathode, wherein the quantum dot light-emitting layer is a quantum dot film prepared by the preparation method according to any one of claims 1 to 7; or the quantum dot light-emitting layer is the quantum dot film according to claim 8.
10. A method for preparing a quantum dot light-emitting diode, characterized in that: At least the process comprises preparing a quantum dot light-emitting layer, and the quantum dot light-emitting layer is a quantum dot film prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Quantum dot light-emitting layer, preparation method thereof and QLED
CN105185918A